Manual de Neuroeducación y Neurociencias del Bilingüismo - Alba Vivancos Sánchez (Language Value)
This review examines Manual de Neuroeducación y Neurociencias del Bilingüismo (Handbook of Neuroeducation and Neuroscience of Bilingualism), co-authored by Dr. Rafael Emilio Bello Díaz and Dr. Karen Bello Llinás. The book, published under the auspices of the Dominican Republic's Vice-Ministry of Supervision, Evaluation and Control of Educational Quality, offers a comprehensive exploration of the neurological and educational dimensions of bilingualism. Divided into ten chapters, it delves into topics such as brain-language interaction, the bilingual mind, neurolinguistics, and executive functions, emphasizing the intersection of neuroscience and language learning.